Floodwater Depth Causes Different Physiological Responses During Post-flooding in Willows - Mozo, Irina; Rodríguez, María E.; Monteoliva, Silvia; Luquez, Virginia M. C. (Frontiers in Plant Science, 2021)
Willows are widely planted in areas under risk of flooding. The physiological responses of willows to flooding have been characterized, but little is known about their responses during the post-flooding period. After the end of the stress episode, plants may modify some traits to compensate for the biomass loss during flooding. The aim of this work was to analyze the post-flooding physiological responses of willow under two different depths of stagnant floodwater. Cuttings of Salix matsudana NZ692 clone were planted in pots in a greenhouse. The experiment started when the plants were 2 months old with the following treatments: Control plants (watered to field capacity); plants partially flooded 10 cm above soil level (F10) and plants partially flooded 40 cm above soil level (F40). The flooding episode lasted 35 days and was followed by a recovery period of 28 days (post-flooding period). After the flooding period, height, diameter and total biomass were higher in F10, while F40 plants showed an increase in plant adventitious root production and leaf nitrogen content. During the post-flooding period, the photosynthetic rate, nitrogen, chlorophyll and soluble sugar contents were significantly higher in leaves of F40 than in Control and F10 treatments. Stomatal conductance and specific leaf area were higher in the previously flooded plants compared to Control treatment. Plants from F10 treatments showed a higher growth in height, root-to-shoot ratio, and carbon isotope discrimination than F40, while the opposite occurred for growth in diameter, vessel size and leaf area. We conclude that depth of floodwater not only causes different responses during flooding, but that its effects are also present in the post-flooding recovery period, affecting the growth and physiology of willows once the stress episode has ended. Even when flooding impacted growth negatively in F40, in the post-flooding period these plants compensated by increasing the photosynthetic rate, plant leaf area and xylem vessel size. Willows endurance to flooding is the result of both responses during flooding, and plastic responses during post-flooding.